2016
DOI: 10.2337/dc16-0941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DECIDE (Decision-making Education for Choices In Diabetes Everyday) Program Delivery Modalities on Clinical and Behavioral Outcomes in Urban African Americans With Type 2 Diabetes: A Randomized Trial

Abstract: OBJECTIVETo compare the effectiveness of three delivery modalities of Decision-making Education for Choices In Diabetes Everyday (DECIDE), a nine-module, literacy-adapted diabetes and cardiovascular disease (CVD) education and problem-solving training, compared with an enhanced usual care (UC), on clinical and behavioral outcomes among urban African Americans with type 2 diabetes.RESEARCH DESIGN AND METHODSEligible participants (n = 182) had a suboptimal CVD risk factor profile (A1C, blood pressure, and/or lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“… 50 There is also initial evidence that patient diabetes self-management programmes focused on barriers to care and social determinants can improve diabetes self-management skills, health behaviours and HbA1c in low-income patients and communities. 51 52 For reference, our results regarding the 2-year incidence of diabetes in high socioeconomic status as compared with low socioeconomic status areas (HR=0.80 and 0.69 in men and women, respectively) have an association with reduced diabetes incidence similar to a 1.2 kg and 2.1 kg reduction in body weight in the DPP trial. 53 Focusing diabetes prevention efforts in lower NSES areas may help in ameliorating health inequalities.…”
Section: Discussionmentioning
confidence: 63%
“… 50 There is also initial evidence that patient diabetes self-management programmes focused on barriers to care and social determinants can improve diabetes self-management skills, health behaviours and HbA1c in low-income patients and communities. 51 52 For reference, our results regarding the 2-year incidence of diabetes in high socioeconomic status as compared with low socioeconomic status areas (HR=0.80 and 0.69 in men and women, respectively) have an association with reduced diabetes incidence similar to a 1.2 kg and 2.1 kg reduction in body weight in the DPP trial. 53 Focusing diabetes prevention efforts in lower NSES areas may help in ameliorating health inequalities.…”
Section: Discussionmentioning
confidence: 63%
“…Patient performance of self-management behaviors, including its effect on clinical outcomes, health status, and quality of life, as well as the psychosocial factors impacting the person's ability to self-manage should be monitored as part of routine clinical care. A randomized controlled trial testing a decision-making education and skill-building program (8) showed that addressing these targets improved health outcomes in a population in need of health care resources. Furthermore, following a DSMES curriculum improves quality of care (9).…”
mentioning
confidence: 99%
“…Having a concrete goal for self-management activities is more beneficial than general, non-specified plan. Not having any plans or not even having a will to make a plan could be an issue about not being prepared for change (Bratzke et al, 2015;Fitzpatrick et al, 2016;Hoffmann et al, 2014). Future plans relate to coping (Hajdarevic, Schmitt-Egenolf, Sundbom, Isaksson, & Hörnsten, 2013) as well as needs to integrate illness and self-management in life (Jutterström, 2013), for example, practical activities such as self-monitoring, taking medication, adjusting diet and exercise if needed.…”
Section: The Smasc Instrumentmentioning
confidence: 99%